Need analysis for workplace English speaking courses for university engineering students in the Kwara state of Nigeria - Solihu, Abdulateef; Abdul Latif @ Bapoo, Lilisuriani (2020)
The globalization of world markets which led to the hegemony of English language over other languages requires graduates from different fields of specialization to equip themselves with English communication skills to communicate effectively in local and international workplace contexts. Thus, this study was conducted to investigate the English speaking skills needed by the engineering students in the Kwara states of Nigeria. A survey was carried out to compare the respondents’ (undergraduate engineering students and industry workers in the Kwara State of Nigeria) self-rating of their speaking interaction and production skills and their perception of the importance of speaking interaction and production sub-skills for workplace communication. The study concluded with suggestions on how to create a better perception of the importance of English speaking skills among engineering students and on how to create a better workplace English curriculum so that the students’ workplace speaking skills can be improved.